2009
DOI: 10.1159/000227998
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Psychometric Tests and Mismatch Negativity in Preschool Children

Abstract: The objective was to determine whether mismatch negativity (MMN) is suitable to supplement subjective psychometric subtests of central hearing. We assessed 13 healthy children and 32 children with central auditory processing disorder (CAPD). Three different types of sound deviants were presented in a multi-deviant MMN design. At group level, the incidence of MMN was always higher in clinically diagnosed controls. Children with better results in the subtest Auditory Memory Span had a higher incidence of MMN. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 86 publications
2
8
0
Order By: Relevance
“…Those potentials reflect semantic, cognitive and attention processes [11]. The results of our study showed that MMN and P300 were more frequent in healthy children than in those with dyslexia, similar to the findings of Sharma et al [14], Bauer et al [18] and Kraus et al [26]. Absent or slight responses of ERPs are thought to be indicative of hearing discrimination problems [1,17].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Those potentials reflect semantic, cognitive and attention processes [11]. The results of our study showed that MMN and P300 were more frequent in healthy children than in those with dyslexia, similar to the findings of Sharma et al [14], Bauer et al [18] and Kraus et al [26]. Absent or slight responses of ERPs are thought to be indicative of hearing discrimination problems [1,17].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have shown that dyslexicchildren display changes in MMN and P300 waves suggesting impaired auditory processing [13,14]. MMN can serve as an early index of evaluation of developmental disorders (dyslexia, language disorders, auditory processing impairment) [15,16,17,18,19]. However, other examinations with ERPs have produced different results: dyslexic children did not differ in terms of MMN and P300 from healthy children [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…deviant stimulus vs. standard stimulus) in the auditory stimulus stream, and its largest amplitude is generally recorded over the fronto-central scalp areas at around 200ms post stimulus (13,14). It represents neurophysiologic changes in the brain's electrical activity in response to auditory discrimination (15), and therefore, it is considered to be an objective measurement to assess the auditory cortical function as well as central auditory processing function (16,17). Cheour et al (17) reported that the MMN presented in 8 of 12 full-term neonates (66.7%) and all of six 3-month-old infants (100%).…”
Section: Furthermore Modern Imaging Techniques Such As Functional Mamentioning
confidence: 99%
“…suggesting that the MMN paradigm has the potential to acquire information on auditory processing capabilities in addition to or instead of psychometric testing. The MMN has therefore also been used in studies on children with central auditory processing disorder (CAPD) (Bauer, Burger, Kummer, Lohscheller, Eysholdt & Doellinger, ), with or at risk of dyslexia (Bruder, Leppänen, Bartling, Csépe, Démonet & Schulte‐Körne, ; Lachmann, Berti, Kujala & Schröger, ; Lovio, Halttunen, Lyytinen, Näätänen & Kujala, ), learning impairment (Kraus, McGee, Carrell, Sharma & Nicol, ), Asperger's syndrome (Korpilahti, Jansson‐Verkasalo, Mattila et al ., ; Kujala,Lepistö, Nieminen‐von Wendt, Näätänen & Näätänen, ), and autism (Gomot, Giard, Roux, Barthélémy & Bruneau, ; Gomot, Blanc, Clery, Roux, Barthelemy & Bruneau, ; Lepistö et al ., ).…”
Section: Introductionmentioning
confidence: 99%